2019
DOI: 10.1093/database/baz125
|View full text |Cite
|
Sign up to set email alerts
|

MIRKB: a myocardial infarction risk knowledge base

Abstract: Myocardial infarction (MI) is a common cardiovascular disease and a leading cause of death worldwide. The etiology of MI is complicated and not completely understood. Many risk factors are reported important for the development of MI, including lifestyle factors, environmental factors, psychosocial factors, genetic factors, etc. Identifying individuals with an increased risk of MI is urgent and a major challenge for improving prevention. The MI risk knowledge base (MIRKB) is developed for facilitating MI resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Myocardial fibrosis has long been a critical component of cardiac remodelling. Myocardial infarction and myocardial fibrosis result in heart failure and death (Bowry et al, 2015; Zhan et al, 2019).…”
Section: Anti‐inflammatory Effect Of Galmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial fibrosis has long been a critical component of cardiac remodelling. Myocardial infarction and myocardial fibrosis result in heart failure and death (Bowry et al, 2015; Zhan et al, 2019).…”
Section: Anti‐inflammatory Effect Of Galmentioning
confidence: 99%
“…Moreover, GAL decreased Bax and caspase-3 gene expression while increasing Bcl-2 in diabetic animals' kidneys (Aladaileh et al, 2021). Myocardial infarction and myocardial fibrosis result in heart failure and death (Bowry et al, 2015;Zhan et al, 2019).…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…A database that integrates the knowledge of NDD risk factors will benefit the systematic understanding of the heterogeneity of the complex NDDs [27] , [28] . We hereby established a knowledge base, NDDRF, which covers different types of NDDs risk factors, such as, epidemiological factors, genetic factors, biochemical factors, combination factors etc ., developing a powerful resource for comparing of risk factor profiles in pan-NDDs level and for the personalized prevention of NDDs.…”
Section: Introductionmentioning
confidence: 99%
“…Risk of MI is seen 10.62% high in male smokers and 7.38% in non-smokers, whereas 5.88% in female smokers and 2.37% in nonsmoker females. Studies conducted in 52 countries shown that men are more prone to high risk compared to women [8]. Age, gender, smoking, high blood pressure, hyperlipidemia, obesity, alcohol consumption family history of heart attack, sedentary life style, stress factors, and comorbidities such as diabetes, COPD, asthma, and chronic kidney disease are considered as risk factors for MI [9].…”
Section: Introductionmentioning
confidence: 99%